Geochemistry of Coastal Permafrost and Erosion-Driven Organic Matter Fluxes to the Beaufort Sea Near Drew Point, Alaska - Bristol, Emily M.; Connolly, Craig T.; Lorenson, Thomas D.; Richmond, Bruce M.; Ilgen, Anastasia G.; Choens, R. Charles; Bull, Diana L.; Kanevskiy, Mikhail; Iwahana, Go; Jones, Benjamin M.; McClelland, James W. (Frontiers in Earth Science, 2021)
Accelerating erosion of the Alaska Beaufort Sea coast is increasing inputs of organic matter from land to the Arctic Ocean, and improved estimates of organic matter stocks in eroding coastal permafrost are needed to assess their mobilization rates under contemporary conditions. We collected three permafrost cores (4.5-7.5 m long) along a geomorphic gradient near Drew Point, Alaska, where recent erosion rates average 17.2 m yr-1. Down-core patterns indicate that organic-rich soils and lacustrine sediments (12-45% total organic carbon; TOC) in the active layer and upper permafrost accumulated during the Holocene. Deeper permafrost (below 3 m elevation) mainly consists of Late Pleistocene marine sediments with lower organic matter content (~1% TOC), lower C:N ratios, and higher δ13C values. Radiocarbon-based estimates of organic carbon accumulation rates were 11.3 ± 3.6 g TOC m-2 yr-1 during the Holocene and 0.5 ± 0.1 g TOC m-2 yr-1 during the Late Pleistocene (12 to 38 kyr BP). Within relict marine sediments, porewater salinities increased with depth. Elevated salinity near sea level (~20-37 in thawed samples) inhibited freezing despite year-round temperatures below 0 °C. We used organic matter stock estimates from the cores in combination with remote sensing time-series data to estimate carbon fluxes for a 9 km stretch of coastline near Drew Point. Erosional fluxes of TOC averaged 1369 kg C m-1 yr-1 during the 21st century (2002-2018), nearly doubling the average flux of the previous half-century (1955-2002). Our estimate of the 21st century erosional TOC flux yr-1 from this 9 km coastline (12,318 metric tons C yr-1) is similar to the annual TOC flux from the Kuparuk River, which drains a 8107 km2 area east of Drew Point and ranks as the third largest river on the North Slope of Alaska. Total nitrogen fluxes via coastal erosion at Drew Point were also quantified, and were similar to those from the Kuparuk River. This study emphasizes that coastal erosion represents a significant pathway for carbon and nitrogen trapped in permafrost to enter modern biogeochemical cycles, where it may fuel food webs and greenhouse gas emissions in the marine environment.